Islam dalam Politik Luar Negeri Singapura - Riyanto, Sugeng; Cipto, Bambang; Warsito, Tulus; Surwandono, Surwandono (Jurnal Hubungan Internasional, 2018)
The Malay Moslem community is actually a minority group in Singapore, which consist 14.3%, while Chinese ethnic is a majority with 76%. The previous studies on minority in Southeast Asia such as Thailand, Philippines and Myanmar showed that mostly the Muslim minority was treated as marginal community and political pressure. This study is to seek whether the Malay Muslim in Singapore has been treated as well as it in neighbor or contrary Malay Moslem has a different position and role in Singaporean politics. Furthermore, in term of foreign policy, this study is going to find the influence of Moslem existance, whereas Singapore is well-known as a secular state. In Singaporean leader’s perspectives, Islam is a threat, as it has been shown in several communal riots during the early history of Singapore, pressure from Malaysia and Indonesia. This is a vulnerable situation for Singapore. Therefore, Singapore addressed moderate policies toward Moslem through accommodation of Islam with several Islamic friendly policies in the country, and accommodation of Malaysian and Indonesian interests. In the other hand, Singapore also anticipates the threat from neighbors through close relations with United States and its allies.